Pengaruh Senam Bugar Lansia Terhadap Perubahan Tekanan Darah Pada Lansia Hipertensi Tahun 2023 - Sasono Mardiono; Arif Irpan Tanjung; Andre Utama Saputra (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Diseases in the elderly tend to degenerative diseases, one of which is hypertension. Handling hypertension non-pharmacologically, among others, by doing fitness exercises for the elderly. Objective: To determine the effect of elderly fitness exercise on reducing blood pressure in the elderly who suffer from hypertension. This study uses a pre-experimental design with a one group pretest-posttest design approach. The sample is the elderly with hypertension who have met the inclusion and exclusion criteria as many as 15 people, which were taken by purposive sampling method. Based on the results of the study using the paired sample t-test. The average systolic and diastolic blood pressure before the elderly fitness exercise was carried out was 156.17/92.30 mmHg. The average systolic and diastolic blood pressure after elderly fitness exercise is 147.98/86.51 mmHg. The results of the study concluded that there was an effect of doing elderly fitness exercises on blood pressure. Suggestion: that the elderly can do fitness exercises for the elderly to changes in blood pressure reduction in the elderly with hypertension.